Enhancing bare land soil quality using electric induction apparatus in combination with rabbit urine liquid fertilizer application to support garlic (Allium sativum) production - Novi Arfarita; Mohammad Jasa Afroni; S Sugiarto; Tsuyoshi Imai (Brawijaya University, 2020)
The new approach in this study was using electric induction technique to enhance soil fertility of bare land in a combination of rabbit urine application in the form of liquid fertilizer. This approach had been exaggerating soil microbial activities and modifying the exchange capacity of anions and cations in soil. This study aimed to find out the best combination of different duration of electricity induction and rabbit urine liquid fertilizer at different levels of their application. Randomized factorial block design with two factors was used for this study. The first factor was the duration of the electric induction at the rates of 0, 30, 45, and 60 minutes, while the application of rabbit urine as liquid organic fertilizer was at the rates of 0, 100, 150, and 200 mL/L. Plant height, number of leaves and stem diameter, fresh and dry weight of garlic bulb were measured within 3 months. The observations were carried out using destructive and non-destructively approached with intervals of 7 days. The best treatment that gave the highest plant height, number of leaves, stem diameter, tuber diameter, fresh and dry garlic bulb and garlic production was found under the combination of 60 minute of electricity induction and 200 mL/L of urine rabbit application (P<0.05). Also, this treatment was successfully to give garlic production of 8.56 t/ha.